Design, synthesis and cytotoxic effects of curcuminoids on HeLa, K562, MCF-7 and MDA-MB‑231 cancer cell lines - Siti Noor Hajar, Zamrus; Akhtar, Muhammad Nadeem; Swee, Keong Yeap; Ching, Kheng Quah; Wan‑Sin, Loh; Noorjahan Banu, Alitheen; Seema, Zareen; Saiful Nizam, Tajuddin; Yazmin, Hussin; Syed Adnan, Ali Shah (Springer Open, 2018)
Background: Curcumin is one of the leading compound extracted from the dry powder of Curcuma longa (Zingib‑eraceae family), which possess several pharmacological properties. However, in vivo administration exhibited limited applications in cancer therapies.